Environmentally Friendly Thermoelectric Materials: High Performance from Inorganic Components with Low Toxicity and Abundance in the Earth. (16th June 2021) - Caballero‐Calero, Olga; Ares, José R.; Martín‐González, Marisol
Abstract: This review article gives an overview of the recent research directions in eco‐friendly, non‐toxic, and earth‐abundant thermoelectric materials. It covers materials such as sulfides, tetrahedrites, earth‐abundant oxides, silicides, copper iodine, Half‐Heusler intermetallic compounds, nitrides, and other environmentally friendly thermoelectrics. In all cases, their history, structure, general characteristics, thermoelectric properties, synthesis methods, and related thermoelectric applications are compiled. It is also shown that they are starting to be an excellent alternative for producing cost‐effective, sustainable, and non‐toxic thermoelectric generators. This review does not try to include all possible materials, but to show that there are high zT thermoelectric materials that are starting to be an excellent alternative for producing cost‐effective, sustainable, and non‐toxic thermoelectric generators. Abstract : This review presents the recent research directions in eco‐friendly, non‐toxic, and earth‐abundant thermoelectric materials. They can be an excellent alternative for producing cost‐effective, sustainable, and innocuous thermoelectric generators. It covers materials such as sulfides, tetrahedrites, earth‐abundant oxides, silicides, copper iodine, Half‐Heusler intermetallic compounds, nitrides, and others.